2013
DOI: 10.1002/ajhb.22418
|View full text |Cite
|
Sign up to set email alerts
|

Different associations of subscapular and triceps skinfold thicknesses with pathogen load: An ecogeographical analysis

Abstract: Across populations, higher pathogen load was associated with reduced central but not peripheral skinfolds, supporting the hypothesis that central adiposity is more closely associated with immune function. This scenario might explain why some populations increase disproportionately in central adiposity when the environment shifts from low-energy high-pathogen status to high-energy low-pathogen status.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
19
0

Year Published

2014
2014
2017
2017

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 27 publications
(21 citation statements)
references
References 113 publications
2
19
0
Order By: Relevance
“…Previous work has shown a tendency for greater overall adiposity (Beall and Goldstein, 1992; Wells, 2012a) and perhaps greater abdominal adiposity in populations from cold climates (Beall and Goldstein, 1992; though see Wells, 2012a). Variation in fat distribution has also been suggested to reflect differences in pathogen load between populations (Wells and Cortina-Borja, 2013). Although we are not aware of good data comparing infectious disease loads in similar populations to those studied here, respiratory infections are reportedly more frequent in the highlands (Way, 1976), suggesting differences in pathogen profiles as well as access to healthcare.…”
Section: Methodsmentioning
confidence: 99%
“…Previous work has shown a tendency for greater overall adiposity (Beall and Goldstein, 1992; Wells, 2012a) and perhaps greater abdominal adiposity in populations from cold climates (Beall and Goldstein, 1992; though see Wells, 2012a). Variation in fat distribution has also been suggested to reflect differences in pathogen load between populations (Wells and Cortina-Borja, 2013). Although we are not aware of good data comparing infectious disease loads in similar populations to those studied here, respiratory infections are reportedly more frequent in the highlands (Way, 1976), suggesting differences in pathogen profiles as well as access to healthcare.…”
Section: Methodsmentioning
confidence: 99%
“…For instance, "long legs", which increases the proportion of children with a low WHZ is found mainly in wealthier families and has been associated with good health [9]. It has been suggested that central fat (influencing WHZ) is predominantly involved in the regulation of the immune response and higher expression of cytokine genes, while peripheral fat (more influencing MUAC) seems more closely related to leptin which also plays a role in the regulation of the immune response but is also linked to survival [10,11].…”
Section: Introductionmentioning
confidence: 99%
“…[64][65][66][67] An eco-261 geographical analysis identified an inverse association between subscapular skinfold 262 thickness and markers of the local pathogen burden, suggesting that populations with high 263 pathogen burdens metabolise central body fat to fund immune function. 68 There is 264 mechanistic support for this hypothesis, as visceral fat has high expression of genes involved 265 in the complement system. 69 Regardless of whether this specific hypothesis is correct, ethnic differences in body fat 281 distribution, lepin and cytokines are already well established.…”
mentioning
confidence: 95%
“…69 Regardless of whether this specific hypothesis is correct, ethnic differences in body fat 281 distribution, lepin and cytokines are already well established. 62,68,71,72 In UK children, the 282 association between adiposity and insulin resistance differs by ethnicity, so that body fat 283 appears to be 'more toxic' in those of South Asian ancestry. 73 Since the energy-deficit 284 imposed by starvation can be assumed to be a human 'constant', and since most starvation 285 deaths occur via infection, the notion that ethnic differences in adipose tissue biology may 286 have been shaped by local infectious disease burdens merits further consideration.…”
mentioning
confidence: 99%